Analisis Yuridis Tanggung Jawab Perdata Terhadap Peredaran Produk Re-Branding di Indonesia: Penelitian - Windi Novita; Anna Triningsih (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The rapid growth of marketplaces as part of electronic commerce in Indonesia has facilitated transactions while simultaneously increasing the circulation of illegal re-branding products that harm consumers. The unclear legal position and civil liability of marketplace operators raise issues of legal certainty, particularly when counterfeit or re-branding products are sold by third-party sellers through digital platforms. This study addresses two main issues: the legal regulation of marketplace operators’ civil liability for the circulation of re-branding products in Indonesia and the implementation of such liability in relation to consumer losses. This research employs a normative legal method using statutory and case approaches, with specific reference to Decision Number 537/Pid.B/2022/PN Jkt.Brt. The findings indicate that the regulation of marketplace civil liability remains fragmented and fails to explicitly define the obligations of marketplace operators in preventing and controlling the distribution of illegal re-branding products. In practice, the implementation of civil liability primarily targets sellers as direct perpetrators, while the role and negligence of marketplace operators in supervision and control are rarely addressed, resulting in ineffective consumer compensation mechanisms.